Myelin-oligodendrocyte glycoprotein antibodies in adults with a neuromyelitis optica phenotype. - Kitley, J; Woodhall, M; Waters, P; Leite, M; Devenney, E; Craig, J; Palace, J; Vincent, A (2012)
OBJECTIVES: To report an association of myelin-oligodendrocyte glycoprotein (MOG) antibodies with aquaporin-4 (AQP4) antibody-seronegative neuromyelitis optica (NMO) and neuromyelitis optica spectrum disorder (NMOSD) in adults. METHODS: We describe the clinical and serologic features of 4 adult patients with an NMO/NMOSD phenotype who had antibodies to MOG. RESULTS: Twenty-seven adult AQP4-seronegative NMO/NMOSD patients were tested for MOG antibodies. Four patients (3 male, 1 female) with severe optic neuritis and/or longitudinally extensive transverse myelitis were positive. All 4 made good recoveries with steroids or plasma exchange. Two patients experienced recurrence of symptoms when corticosteroids were withdrawn quickly but none have experienced further relapses over a mean follow-up of 12 months, although 3 patients remain on treatment. Imaging abnormalities resolved fully following clinical recovery and MOG antibody titers fell in all 4 patients. MOG antibodies were not found in 44 AQP4 antibody-positive NMO/NMOSD patients, 75 adult patients with multiple sclerosis, or 47 healthy individuals. CONCLUSIONS: MOG antibody-associated NMO/NMOSD could account for some cases thought previously to be AQP4-seronegative NMO/NMOSD. Our 4 patients appear to have more favorable clinical outcomes than those with typical AQP4 antibody-mediated disease. However, further studies of NMO/NMOSD and other demyelinating conditions are required to help clarify the diagnostic and prognostic relevance of MOG antibodies.